Общественное мнение о социополитическом устройстве Украины - Оссовский, В. (Социология: теория, методы, маркетинг, 2000)
The notion of “Ukraine’s social order” as seen by the subjects of public opinion directly influences the process of state creation, scenario implementation, social structure transformation and cultural factors regulating these subjects’ behavior. The data concerning such vision of the desired reality presented in the article were received in the process of public opinion monitoring carried out by the author in 1995–1999. The paper contains information on the preferences of the public opinion leaders as to the desired directions of Ukraine’s development, the criteria of attractiveness of alternative socio-economic and socio-political models of the country’s social future. The monitoring data are examined in the context of interrelation with the national idea, the state of public opinion in Ukraine in general, ideological statements of its political establishment in particular.